2007
DOI: 10.1111/j.1570-7458.2007.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐related life history traits in interspecific hybrids of cactophilicDrosophila

Abstract: In the genus Drosophila (Diptera: Drosophilidae), interspecific hybridization is a rare phenomenon. However, recent evidence suggests a certain degree of introgression between the cactophilic siblings Drosophila buzzatii Patterson & Wheeler and Drosophila koepferae Fontdevila & Wasserman. In this article, we analyzed larval viability and developmental time of hybrids between males of D. buzzatii and females of D. koepferae , raised in media prepared with fermenting tissues of natural host plants that these spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“…Studies of natural populations in the field and under laboratory conditions have shown that D. buzzatii and D. koepferae differ in their preferences regarding oviposition sites (Soto et al ., ) and higher viabilities, faster developing times and increased mating success for both species were observed when they were reared in their respective primary hosts (Soto et al ., ; Hurtado et al ., ). Here we enlarged the list of traits in which host‐dependent phenotypic plasticity is displayed by D. buzzatii whereas D. koepferae showed a more canalized behavior as previously observed for viability, developmental time (Soto et al ., ,b, , ), starvation resistance, oviposition preference (Soto et al ., ), and genital morphology (Soto et al ., ). As a performance‐related trait, time of pupal emergence was positively correlated with developmental time and negatively correlated with adult wing size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of natural populations in the field and under laboratory conditions have shown that D. buzzatii and D. koepferae differ in their preferences regarding oviposition sites (Soto et al ., ) and higher viabilities, faster developing times and increased mating success for both species were observed when they were reared in their respective primary hosts (Soto et al ., ; Hurtado et al ., ). Here we enlarged the list of traits in which host‐dependent phenotypic plasticity is displayed by D. buzzatii whereas D. koepferae showed a more canalized behavior as previously observed for viability, developmental time (Soto et al ., ,b, , ), starvation resistance, oviposition preference (Soto et al ., ), and genital morphology (Soto et al ., ). As a performance‐related trait, time of pupal emergence was positively correlated with developmental time and negatively correlated with adult wing size.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in the vast areas where both species occur in sympatry, a certain degree of overlap in host exploitation occurs, with the 2 species emerging from both resources despite maintaining a preference for their respective primary host (Hasson et al ., ; Soto et al ., ). Previous studies showed that traits associated to fitness were maximized when flies were reared in their primary hosts (Soto et al ., ,b, , ; Hurtado et al ., ). Developmental instability levels increased when flies of both species were reared in their respective secondary host (Soto et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila have served as an important model system for studies of speciation, but few studies have examined the possible role of ecology in post‐zygotic isolation (but see Soto et al. , 2007a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Both mechanisms, separately or combined, can shape habitat selection and influence the evolution of species by promoting host specialization and contributing to the origin of new species (Feder and Forbes 2008). Previous studies in D. buzzatii and D. koepferae revealed the paramount importance of the host plant on wing and genital morphology, viability and developmental time (Fanara et al 1999;Soto et al 2007Soto et al , 2008a. Also, there is evidence that these species differ in their preferences for egg laying sites (Fanara and Hasson 2001).…”
Section: Introductionmentioning
confidence: 94%